Infrared Drying of Button Mushroom Slices - Doymaz, Ibrahim (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2014)
The effect of different infrared power levels on the drying kinetics of button mushrooms was investigated. Mushroom slices were dried at infrared power levels of 83, 125, 167, and 209 W. The power level affected the drying and rehydration characteristics of mushroom slices. Drying time was reduced from 300 min to 40 min as the infrared power level increased from 83 to 209 W. Mathematical models frequently used to represent drying of agricultural products were fitted to experimental data of mushroom drying. The parabolic model was the best for representation of mushroom drying. Effective moisture diffusivity varied from 3.81 x10(-10) to 4.20x10(-9) m(2)/s over the infrared power levels used. The activation energy was estimated using a modified Arrhenius-type equation and calculated to be 7.55 kW/kg.
Keywords: activation energy; effective moisture diffusivity; infrared drying; mathematical modelling; mushroom slice; MICROWAVE-VACUUM; POTATO SLICES; APPLE POMACE; KINETICS; PRETREATMENTS; RADIATION; BEHAVIOR; QUALITY; MODELS; Food Science & Technology